2018
DOI: 10.1590/s0100-204x2018001000004
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of teak stands at different spacing

Abstract: The objective of this work was to evaluate the growth and yield of teak (Tectona grandis) stands at different spacing and in different soil classes. Twelve spacing were evaluated in an Inceptisol and Oxisol, in plots with an area of 1,505 or 1,548 m2, arranged in a completely randomized design with nine replicates. The teak trees were measured at 26, 42, 50, and 78 months of age. Total tree height was less affected by spacing. Mean square diameter was greater in wider spacing, whereas basal area and total volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
2
2
0
3
Order By: Relevance
“…Narrow spacing has a higher tree height value than wide, except for spacing 3 m x3 m, and this is consistent with Berrocal et al (2020), where stand density also showed a statistically significant effect not only with DBH but also with high growth (Berrocal et al 2020). Differences in height growth in teak were influenced by site quality (Cardoso et al 2013;Medeiros et al 2018) and genetics .…”
Section: Effect Of Spacing On Teak Growthsupporting
confidence: 66%
“…Narrow spacing has a higher tree height value than wide, except for spacing 3 m x3 m, and this is consistent with Berrocal et al (2020), where stand density also showed a statistically significant effect not only with DBH but also with high growth (Berrocal et al 2020). Differences in height growth in teak were influenced by site quality (Cardoso et al 2013;Medeiros et al 2018) and genetics .…”
Section: Effect Of Spacing On Teak Growthsupporting
confidence: 66%
“…This finding also suggests that In contrast, spacing has no significant effect on the height growth of teak (p-value) (Table 3), with the best of spacing for height growth being 8 m × 2 m (Figure 8). This result may have occurred probably because height growth is affected by site quality (Malimbwi et al, 1992;Cardoso et al, 2013;Medeiros et al, 2018), thereby indicating that the height growth of teak is not affected by stand density (Cardoso et al, 2013;Medeiros et al, 2018), but the height growth is sensitive to differences in site quality. Ola-Adams (1990) examined the effect of spacing on the growth and yield of Tectona grandis and Terminalia superba.…”
Section: Resultsmentioning
confidence: 99%
“…Verifica-se, no entanto, que os povoamentos de Teca apresentam produtividade variável, muitas vezes relacionada à seleção de sítios impróprios para o desenvolvimento, práticas de manejo e seleção do material genético inadequados (MEDEIROS, 2018). Segundo Rocha et al (2015), ainda há falta de informação e pouco investimento em pesquisa sobre a Teca relacionadas às práticas silviculturais, como a condução de plantios comerciais, características edafoclimáticas específicas e viabilidade econômica da atividade.…”
Section: Introductionunclassified